PLANNING AND EVALUATION OF FTTB NETWORK USING THE GPON METHOD AT THE MEDAN STATE POLYTECHNIC - Mutiara Widasari Sitopu; Charla Tri Selda Manik; Muhammad Sukri Habibi Daulay; Ummu Handasah (Jurnal Penelitian, 2025)
This research examines the design of a Fiber to the Building (FTTB) network based on Gigabit Passive Optical Network (GPON) technology using OptiSystem and Google Earth Pro. The network design and simulation were conducted for the Civil Engineering Department Building and the Telecommunication Laboratory Building at Politeknik Negeri Medan. Network performance was evaluated based on received optical power, attenuation, Bit Error Rate (BER), and Q-Factor. The simulation results show that the received optical power ranged from −19 dBm to −21 dBm. The total attenuation from the OLT to ONT1 through ODP1 was 22.601 dB, while the attenuation from the OLT to ONT2 through ODP2 was 21.588 dB. Both values were below the maximum optical loss budget of 28 dB used for GPON Class B+ evaluation. The obtained BER values ranged from 10⁻³⁷ to 10⁻²⁶, which were significantly lower than the feasibility criterion of 10⁻⁹. The Q-Factor values were also higher than the minimum criterion of 6. Based on the analysis, the designed FTTB network provides good signal quality and meets the technical feasibility criteria used in this study.